Promotion of humanized care to the family by the nursing team in neonatal unit - Rosemary dos Santos Rocha; Ingrid Martins Leite Lúcio; Márcia Maria Coelho Oliveira Lopes; Claúdia Regina de Castro Lima; Alisson Salatiek Ferreira de Freitas (Rev Rene)
We aimed to know the perception of the nursing team on humanized care to the family of newborn admitted in the Neonatal Care Unit (NCU); to identify nursing actions that promote the humanization of assistance and to investigate factors that raise difficulties to the family care in the neonatal context. This is a descriptive study carried out in a public maternity in February and March 2008, in Fortaleza-CE-Brazil. For data collection were used non-participant observation and semi-structured interviews with 25 nursing professionals (nurses, technicians and nursing assistants) in their work environment. Three categories emerged from data analysis: Conceptions of the nursing team as to humanized care at NCU; nursing interventions to the family as well as intervening factors in humanized care. We so concluded that the nursing team together with the assistance provided to newborns should have a pleasant and caregiver posture with the family, supporting them to participate in this process of looking after the patient in the neonatal environment.